2013
DOI: 10.3758/s13414-013-0443-z
|View full text |Cite
|
Sign up to set email alerts
|

Music can elicit a visual motion aftereffect

Abstract: Motion aftereffects (MAEs) are thought to result from the adaptation of both subcortical and cortical systems involved in the processing of visual motion. Recently, it has been reported that the implied motion of static images in combination with linguistic descriptions of motion is sufficient to elicit an MAE, although neither factor alone is thought to directly activate visual motion areas in the brain. Given that the monotonic change of musical pitch is widely recognized in music as a metaphor for vertical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 39 publications
0
10
1
Order By: Relevance
“…Kitagawa and Ichihara (2002) concluded that this finding supports the notion of visual dominance over auditory perception for spatial events. This finding is in contrast, however, with those of Maeda et al (2004) who found that auditory stimuli consisting of sounds increasing or decreasing in pitch was sufficient to induce cross-modal changes in visual motion perception in the vertical plane (Maeda et al, 2004), as well as findings by Hedger et al (2013) who found that music containing ascending or descending scales can induce visual MAEs in the vertical plane (Hedger et al, 2013). However, these studies rely on the metaphorical relationship between a sound and an associated visual representation rather than on physical motion cues of the sounds themselves.…”
Section: Introductioncontrasting
confidence: 72%
See 3 more Smart Citations
“…Kitagawa and Ichihara (2002) concluded that this finding supports the notion of visual dominance over auditory perception for spatial events. This finding is in contrast, however, with those of Maeda et al (2004) who found that auditory stimuli consisting of sounds increasing or decreasing in pitch was sufficient to induce cross-modal changes in visual motion perception in the vertical plane (Maeda et al, 2004), as well as findings by Hedger et al (2013) who found that music containing ascending or descending scales can induce visual MAEs in the vertical plane (Hedger et al, 2013). However, these studies rely on the metaphorical relationship between a sound and an associated visual representation rather than on physical motion cues of the sounds themselves.…”
Section: Introductioncontrasting
confidence: 72%
“…However, these studies rely on the metaphorical relationship between a sound and an associated visual representation rather than on physical motion cues of the sounds themselves. In this way, the findings of Maeda et al (2004) and Hedger et al (2013) are much like the positive aftereffects (i.e., changes in visual motion perception in the same direction as the adapting auditory stimulus) found in the sound contingent visual motion aftereffect (Hidaka et al, 2011a), and the negative aftereffects (i.e., changes in visual motion perception in the opposite direction as the adapting auditory stimulus) found for verbal language descriptions of visual events (Dils and Boroditsky, 2010), respectively. Furthermore, the looming/receding auditory motion stimuli used in Kitagawa and Ichihara's (2002) study were simply tones increasing or decreasing in volume and provided weak motion cues compared to those from veridical horizontal auditory motion (Carlile and Leung, 2016).…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…While the Poisson-like PPC framework does account for several important aspects of multisensory cue combination, some of its underlying assumptions may not always be valid. For example, neural weights appear to depend on stimulus reliability in MSTd [4**, 24], and although the theory assumes unisensory representations are independent, sensory interactions may begin before multisensory integration occurs [58*, 59]. Furthermore, computations like causal inference cannot be performed explicitly using Poisson-like PPCs [60].…”
Section: Discussionmentioning
confidence: 99%